САҲРАДАҒЫ МУҲАББАТ ДӘСТАНЫ (К.Рахмановтың «Шөл дәстаны» поэмасында конфликт ҳәм характер) - Дабылов, П.А. (FAN va JAMIYAT, 2016)
The article deals with the analysis of questions of conflict and character in the poem ― The Legend of Desert‖ by the famous Karakalpak poet Kenesbay Rakhmanov. In the focus of attention is the study of the role of conflict in forming the characters of heroes in the poem and the genre peculiarities of the poem.